Investigating Lesion Volume and Localization Effects on Developmental and Adult Motor Impairments in a Mouse Model of Perinatal Stroke - Romero Quineche, Beatriz (Université d'Ottawa / University of Ottawa, 2024)
Perinatal stroke is a subtype of stroke causing substantial lifelong morbidity in children often presenting as neurodevelopmental delays and sensorimotor impairments. Rodent models that present long-lasting motor impairments after perinatal stroke can be used to evaluate the relationship between injury parameters (size and location) and behavioural function. On postnatal day 7, a unilateral photothrombotic stroke was induced in the primary motor cortex of mice. To evaluate sensorimotor function during early development and adulthood, we used a series of behavioural tests. We hypothesized that pre-weaning behavioural tests will provide a direct measure of sensorimotor deficits induced by the stroke, while behavioural tests in adulthood will be influenced by endogenous plasticity and recovery processes. Interestingly, we found that both pre-weaning and adult behavioural assays revealed impairments. In the pre-weaning tests, impairments were observed in grip strength and hindlimb suspension tests. During adulthood, stroke animals demonstrated significant impairments in the contralesional limb in both the grid walk and the cylinder tests. Furthermore, performance on the grid walk test had a significant positive correlation between the number of miss-steps by the impaired forelimb with lesion volume. Finally, using a semi-automated lesion localization workflow, we were able to characterize the extent of injury with precision to understand its impact on various brain regions and its correlation to functional outcomes. The severity of injury in different brain regions proved to be significant for outcomes observed in the grid walk test. Overall, our perinatal stroke model produced long-lasting impairments that can be detected using both pre-weaning and adult behavioural assays. By performing precise characterization of the lesion, we were able to demonstrate that lesion size and location can be used as relevant predictors of perinatal stroke outcome.
Keywords: Perinatal Stroke; Motor Deficits; Grid Walking Task; Cylinder Task; Pre-weaning Behavioural Tests; Rodent Model; Developmental Brain Injury; Longitudinal Behavioural Study; Neural Reorganization; Forelimb Suspension Test; Hindlimb Suspension Test; Grip Strength Test; Post-stroke recovery; Lesion Volume